XIV International Scientific Conference (3z(BINTERAGROMASH 2021(3ys Precision Agriculture and Agricultural Machinery Industry, Volume 2 - Beskopylny, Alexey; Shamtsyan, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book contains proceedings of the International Scientific Conference on Precision Agriculture and Agricultural Machinery Industry INTERAGROMASH 2021. It is a collection of original and fundamental research papers in areas such as agricultural machinery, agricultural materials science, construction of agricultural facilities, training of specialists in the field of agriculture, and other topics. Each of the presented chapters has undeniable scientific value and novelty in the corresponding research areas. The book is aimed for professionals and practitioners, for researchers, scholars, and producers. The materials presented here can be used in the educational process at specific agricultural universities or during vocational training at enterprises and will become an indispensable helper to farm managers in making the best agronomic decisions. The book is also useful for representatives of regional authorities, as it gives an idea of existing high-tech solutions for agriculture.
High-Speed HFC-boriding Kinetics -- Optimal Heat Flux Reduction Inside Film Cooled Wall -- Numerical Simulation of the Operation of a Chemical Reactor with an Open Cell Foam Catalyst -- The Cost of Flexible Elements of a Rectangular Profile -- Biodiesel Production from Various Crops -- Molecular Relaxation in a Liquid Crystal after Switching off the Acoustic Action -- Microstructure and Composition of Boriding Coating Based on Boron Carbide and Amorphous Boron -- The Stress State of Corner Cutout Area of the Model Boundary by Photoelastic Method -- Influence of the Particle Number on Mixture Quality -- Increasing the Efficiency of Calculation of Magnetic Fields of Magnetostriction Level Gauges -- Specific Features of Surface Morphology During Plasma Electrolytic Processing -- LU-factorization of the System of Magnetic Field Equations of Magnetostrictive Level Transducers.
Keywords: Manufactures; Computational intelligence; Agriculture; Machines, Tools, Processes; Computational Intelligence; Agriculture; Agricultural engineering -- Congresses; Precision farming -- Technological innovations -- Congresses